Spirituality and Islamic Business Ethics: A Phenomenological Study of a Muslim Manager at PT Indoboiler in Indonesia - Muhamad Hilmi Pauzian (Gunung Djati Conference Series, 2026)
In a contemporary business environment where material success is often prioritized, spirituality offers an important ethical foundation for Muslim entrepreneurs. This study explores how Islamic spirituality is internalized and embodied in the business practices of a Muslim manager at PT Indoboiler, Bekasi, Indonesia. Using a qualitative approach, this study adopts phenomenology based on Alfred Schutz's theory of the construction of meaning to analyze subjective experience. Data were collected through direct observation and in-depth interviews with key informants who were known to exhibit consistent spiritual behaviors, supported by additional interviews with Foundation employees and caregivers. The findings revealed that the informant's spiritual orientation was shaped by internalized religious values, a supportive religious environment, the influence of moral role models (teachers), and strong internal motivations. Spirituality in business is expressed through faith, piety, ethical behavior, and a constant awareness of God's presence. Business activities are seen not only as a means of profit, but as a form of worship oriented towards eternal success in the hereafter. The study concludes that spirituality serves three key functions in ethical Muslim entrepreneurship: as a regulator of behavior, an emotional stabilizer, and a source of creative energy. These insights contribute to the growing literature on Islamic business ethics by providing context-rich empirical data on spiritual experiences lived in the workplace.